Role of Pharmacists in Antimicrobial Stewardship During COVID-19 Outbreak: A Scoping Review - Kusuma IY; Pratiwi H; Pitaloka DAE (Journal of Multidisciplinary Healthcare, 2022)
Ikhwan Yuda Kusuma,1,2 Hening Pratiwi,3 Dian Ayu Eka Pitaloka4,5 1Institution of Clinical Pharmacy, Faculty of Pharmacy, University of Szeged, Szeged, 6725, Hungary; 2Pharmacy Study Program, Faculty of Health, Universitas Harapan Bangsa, Purwokerto, 53182, Indonesia; 3Department of Pharmacy, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, 53122, Indonesia; 4Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, 45363, Indonesia; 5Center of Excellence in Higher Education for Pharmaceutical Care Innovation, Universitas Padjadjaran, Sumedang, 45363, IndonesiaCorrespondence: Dian Ayu Eka Pitaloka, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Sumedang, West Java, 45363, Indonesia, Tel +62 22-84288812, Email dian.pitaloka@unpad.ac.idAbstract: Since the beginning of the coronavirus disease 2019 (COVID-19) pandemic, pharmacists have been on the front lines of health care, offering vital services. Consequently, the need for pharmacists to support an effective antibiotic stewardship (AMS) program during the COVID-19 outbreak has become increasingly evident. This scoping review was performed to examine related articles in 2020– 2022 published in the Scopus, SAGE, and Cochrane databases with the keywords “Pharmacist” and “Antibiotic Stewardship” and “COVID-19”. The inclusion criteria were full-text articles written in English. A total of 15 articles were included in this review to describe the role of pharmacists in AMS during the COVID-19 outbreak. In general, pharmacists are responsible for identifying and treating patients during pandemics, ensuring the continued supply and accessibility of medications, promoting health policies, and monitoring antibiotic use for COVID-19 cases and co-infections. At the hospital, as the most significant element for pharmacists on the AMS team, the apparent change is demonstrated in educating patients on telehealth services, clarifying misconceptions about treatments and antibiotic consumption, as well as taking a leadership position to establish local guidelines for the COVID-19 treatment protocol. Pharmacists have an important role in the AMS program, and the COVID-19 pandemic was perceived as a highlight their importance. Therefore, their work with the AMS program needs to be improved as they learn to extend their role in telehealth services, educate and clarify the misconceptions about COVID-19 treatments and other antibiotic consumption in the community, inventory control the COVID-19 drug, antibiotics, and vaccine, as well as take the lead in establishing local guidelines on antibiotic consumption during the pandemic outbreak.Graphical Abstract: Keywords: pharmacists, antibiotic stewardship, COVID-19